Do positive emotions prompt students to be more active? Unraveling the role of hope, pride, and enjoyment in predicting Chinese and Iranian EFL students' academic engagement - Derakhshan, Ali; Yin, Hongbiao (Journal of multilingual and multicultural development, 2025)
Drawing on the control-value theory, this cross-cultural research inspected the association between positive activating emotions, namely pride, hope, and enjoyment, and academic engagement among Chinese and Iranian EFL students. This study also looked into the role of these positive emotions in predicting Chinese and Iranian students' academic engagement. Using a maximum variation sampling technique, 346 Chinese and 353 Iranian EFL students were chosen from various colleges and universities. Afterward, an online survey was sent to participants via email and common messaging apps. Following that, structural equation modelling and confirmatory factor analysis were conducted through AMOS software to analyse participants' answers. The results obtained from CFA and SEM indicated that Chinese and Iranian students' academic engagement is closely related to their feelings of pride, hope, and enjoyment. The results also demonstrated that pride, hope, and enjoyment can meaningfully and favourably predict Chinese and Iranian students' academic engagement. Interestingly, no significant difference was discovered between the Chinese and Iranian measurement models. These outcomes add to the existing body of literature on the interplay between positive activating emotions and students' academic behaviours.